The Impact Of User Interface Design Element For Doctor Satisfaction On Electronic Medical Record System - Zakaria, Nuur Farhana Shatilah (2016)
The user interface has slowly become one of the primary reasons for the users to refuse to use the electronic medical record (EMR) system even in a forceful way. The interface design not only affecting the daily tasks, but also patient-doctor relationship. This research is aimed to produce a validated user interface design of an EMR system. In order to understand the problems, it is best to know the user requirement versus real required demand for both EMR system and user interface design. Most of EMR system that develops nowadays were designed based on developer imagination and senior doctors as an advisor (system requirement) but not based on current technology and young doctor's opinion. It is often mentioned that opinion from experience user is the best, but the results prove otherwise especially in user interface design. A number of 93 participants of future doctors from MMMC, medical staffs from UTeM Clinic and 1PHRS a BIOCORE health care system participate in this research.Therefore, the user requirement of the system funtion is gained from an experience doctor and young doctor by using the participitory approach.The new idea is acceptable but the doctor refuse to make changes in their current system because they require more time to adapt to the changes and this idea are not yet implemented in the working system.Hopefully, the proposed interface can improve the patient-doctor relationship and ease the daily tasks.